2019
DOI: 10.3389/fpls.2019.01172
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Phosphorus, Zinc, and Iron Homeostasis in Nonmycorrhizal and Mycorrhizal Plants

Abstract: Phosphorus (P), zinc (Zn), and iron (Fe) are three essential elements for plant survival, and severe deficiencies in these nutrients lead to growth retardation and crop yield reduction. This review synthesizes recent progress on how plants coordinate the acquisition and signaling of Pi, Zn, and Fe from surrounding environments and which genes are involved in these Pi–Zn–Fe interactions with the aim of better understanding of the cross-talk between these macronutrient and micronutrient homeostasis in plants. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 214 publications
(307 reference statements)
0
59
0
Order By: Relevance
“…PHR1 seems to be a positive regulator of the ZIP transporters (AtZIP2 and AtZIP4) under Pi deficiency in Arabidopsis (Briat et al, 2015). The cross-talk of signals between P, Zn, and Fe were highlighted by many articles (Briat et al, 2015;Xie et al, 2019). Only a very little research is done on the characterization Zn responsive and ZIP related TFs in crops and most of the reports are also confined only to plants like Arabidopsis.…”
Section: Regulation Of Zip Transporters In Plantsmentioning
confidence: 99%
“…PHR1 seems to be a positive regulator of the ZIP transporters (AtZIP2 and AtZIP4) under Pi deficiency in Arabidopsis (Briat et al, 2015). The cross-talk of signals between P, Zn, and Fe were highlighted by many articles (Briat et al, 2015;Xie et al, 2019). Only a very little research is done on the characterization Zn responsive and ZIP related TFs in crops and most of the reports are also confined only to plants like Arabidopsis.…”
Section: Regulation Of Zip Transporters In Plantsmentioning
confidence: 99%
“…Zinc deficiency can cause compromised immune responses, stunting during childhood, and increased risk of child mortality (Micronutrient_Initiative, 2009;Livingstone, 2015). While crosstalk between Fe, Zn, P, and S signaling in plants is recognized, not much is known in C 3 or C 4 plants regarding the mechanistic integration of these signaling networks (Mendoza-Cozatl et al, 2019;Xie et al, 2019). However, it was recently proposed that Fe, Zn, P, and S signaling are integrated in a PHR1 dependent manner in the C 3 plant Arabidopsis (Briat et al, 2015).…”
Section: How Does Elevated Co 2 Affect Micronutrients In C 3 and C 4 mentioning
confidence: 99%
“…Singh et al (1986) reported that applied P increased soil P levels and tissue P concentration, but resulted in a significant decrease of tissue Zn levels. The current global thrust is on identification of genes important for interactions between Pi, Zn and/or Fe transport and signaling is a useful target for breeders for improvement in plant nutrient acquisition (Xie et al, 2019). However, this recognition of the negative interaction has gone too far and farmers are not applying enough P and Zn in their fields, despite majority of soils testing low to medium in available P (Tandon, 1987) and about 50 per cent of the soils in India testing low in available Zn (Singh, 2009) and good responses of most crops to P (Blaise et al, 2014) and Zn (Rattan et al, 2008;Patel, 2011) have been reported.…”
Section: Reaction With Micronutrients Other Than Fementioning
confidence: 99%